TRH Analog, Taltirelin Improves Motor Function of Hemi-PD Rats Without Inducing Dyskinesia via Sustained Dopamine Stimulating Effect - Zheng, Cong; Chen, Guiqin; Tan, Yang; Zeng, Weiqi; Peng, Qiwei; Wang, Ji; Cheng, Chi; Yang, Xiaoman; Nie, Shuke; Xu, Yan; Zhang, Zhentao; Papa, Stella M.; et al. (Frontiers in Cellular Neuroscience, 2018)
Thyrotropin-releasing hormone (TRH) and its analogs are able to stimulate the release of the endogenic dopamine (DA) in the central nervous system. However, this effect has not been tested in the Parkinson’s disease (PD), which is characterized by the DA deficiency due to the dopaminergic neurons loss in the substantia nigra. Here we investigated the therapeutic effect of Taltirelin, a long-acting TRH analog on 6-hydroxydopamine-lesioned hemi-Parkinsonian rat model. 1-10 mg/kg Taltirelin i.p. administration significantly improved the locomotor function and halted the electrophysiological abnormities of PD animals without inducing dyskinesia even with high-dose for 7 days treatment. Microdialysis showed that Taltirelin gently and persistently promoted DA release in the cortex and striatum, while L-DOPA induced a sharp rise of DA especially in the cortex. The DA-releasing effect of Taltirelin was alleviated by reserpine, vanoxerine (GBR12909) or AMPT, indicating a mechanism involving vesicular monoamine transporter-2 (VMAT-2), dopamine transporter (DAT) and tyrosine hydroxylase (TH). The in vivo and in vitro experiments further supported that Taltirelin affected the regulation of TH expression in striatal neurons, which was mediated by p-ERK1/2. Together, this study demonstrated that Taltirelin improved motor function of hemi-PD rats without inducing dyskinesia, thus supporting a further exploration of Taltirelin for PD treatment.